Enclosure Quality of Public Open Space in Sukarno Hatta Street Corridor, Malang City - I Kadek Rama Saputera; Jenny Ernawati (Jurnal Mahasiswa Jurusan Arsitektur, 2020)
Public open space is a vital city element, especially street corridors. The main streetcorridors in Malang City are generally located in commercial areas, especially on theSukarno Hatta Street Corridor. This corridor has various potentials, but the accelerationof development has an impact on the physical aspects of the varying heights and setbacksof buildings so that it cannot accommodate the enclosure quality well. The research wasconducted by measuring the physical aspects of the enclosure in the study area, namelythe height and setback of street walls and the width of the floor. Calculation ofthe enclosure degree used the d / h ratio (the distance to the height of the street wallsfacing each other). The analysis stage consists of the data classification stage, overlaydata, street cluster determination, enclosure degree determination, and enclosure qualityanalysis. The data synthesis was done by compiling the analysis' results. The resultsshowed in this corridor was dominated by the "weak" enclosure quality category (2 m <d/ h≤4 m). Adjusting the characteristics of the zone and function of the building, theheight, and the setback of vegetation, fences, and buildings can improve the enclosure quality.